Enteroparasitosis detection human and sources of environmental pollution in river Chagres, Panama (Revista Venezolana de Salud Pública, 2018)
In tropical countries like Panama, parasitism levels reach values intimidating, especially in indigenous areas. This is mainly due to the lack of adequate sanitary facilities to prevent the acquisition of Enteroparasites. Detection of parasites in feces was performed in 74 individuals (aged between two months and 76 years) by two methods, direct stool examination in triplicate and the concentration method and Willis Ritchie Molloy. The prevalence was 89,2 % with no significant association between women and men (47,3 % vs. 41,9 %). Children 5 to 9 years showed the highest percentage of parasitism (22,1%). Protozoa predominated (90,3%) of helminths (9,7%). To detect the presence of parasites in 10 samples of 100g ground floor in each community, which was applied The Ritchie and Willy- Molloy, to identify the parasitic forms were taken microscopically. The 90% of the samples were positive for some parasitic form. As for the presence of parasites in 10L water 10 water samples were taken from each community to which was applied The Ritchie and Willy- Molloy, to identify microscopic parasitic forms. The 100% of samples were positive for some parasitic form.
Keywords: Intestinal parasites; iIndigenous communities; Environmental factors; Chagres River